Utilização do Sketchup no ensino de geometria espacial - Santos, José Aparecido Sousa (2015)
Technological resources are providing changes in the education, contributing to improving the teaching-learning process, particularly in mathematics. This paper aims to present an innovative methodology with the help of SketchUp software covering the main contents of spatial geometry in high school. We propose different activities, based on references, favoring the user to acquire knowledge, skills and abilities to build three-dimensional objects and analyze their properties. Also, make it more attractive and dynamic the mathematics classes. Thus, we present na alternative to enrich the teaching-learning process of spatial geometry from these educational innovations.